(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2008)
Teeth are an excellent material in living and non-living populations for anthropological, genetic, odontologic and forensic investigations. To define the morphometric criteria for teeth in Haryana, the present study has been conducted in 102 patients (M:F – 52:50) in the age group of 17-28 years. It was seen that statistically significant sexual dimorphism exist in the mandibular canine and intercanine distance weather measurements are taken on casts or intra-orally. It is concluded that whenever the mesio-distal diameter of mandibular canine is greater than 7.2 mm, the probability of sex being male is hundred percent. If the intercanine distance is greater than 25 mm, the age of male and female is more than 14 and 12 years in male and female respectively.